Huntington Beach Fourth of July Parade on Main Street - Watkins, Howard::::::::: (1983)
Christine Watkins holding Robin Watkins reaching for string held by Adam Watkins Adam wearing blue U.C. Berkeley hoodie sweatshirt; red paint marks on face from Indian Guides